Pengaruh Model Discovery Learning terhadap Keterampilan Berpikir Kritis: Studi Meta-Analisis - Bettri Yustinaningrum (Malewa: Journal of Multidisciplinary Educational Research, 2025)
The variability of research findings regarding the effectiveness of the discovery learning model on students’ critical thinking skills indicates the need for a comprehensive synthesis to obtain a more conclusive understanding. In response to this gap, the present study employs a meta-analysis approach to calculate and compare the effect sizes reported in previous studies. The primary objective of this research is to provide an empirical overview of the effectiveness of the discovery learning model in improving critical thinking skills. This study follows a systematic procedure based on the PRISMA guidelines, starting from the identification and screening stages to the selection of studies that meet the inclusion criteria. Through this process, a total of 13 journal articles and 1 conference proceeding published between 2018 and 2023 were included. All eligible data were analyzed using the OpenMEE software to compute the effect size and statistical significance. The results of the meta-analysis show a p-value of 0.002, which is lower than the significance threshold of 0.05. This indicates that the discovery learning model has a significant impact on enhancing students’ critical thinking abilities. Furthermore, the estimated effect size of 0.889 falls within the medium-to-high category, reinforcing the conclusion that the model provides a substantial contribution to the development of critical thinking skills. Based on these findings, it can be concluded that the discovery learning model is an effective instructional approach for improving critical thinking.